Peningkatan Kompetensi Guru SMP Negeri 12 Yogyakarta dalam Membuat Bahan Ajar Digital dengan Canva - Satriyo Agung Dewanto; Bekti Wulandari; Bonita Destiana; Agus Qomaruddin Munir; Muhammad Resa Arif Yudianto; Dzul Fadli Rahman; Ramadhana Setiyawan (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
Digital transformation requires teachers to be able to develop innovative and interactive teaching materials. However, limited competence in utilizing modern design platforms remains an obstacle at SMP Negeri 12 Yogyakarta. This community service program aims to improve teachers' skills in creating interactive digital teaching materials using the Canva platform. The method utilized was a hands-on workshop with a mixed-methods evaluation approach, including pre-tests, post-tests, product assessments, and feedback questionnaires. The evaluation results showed a significant increase in competence among all participants, as evidenced by a surge in post-test scores, the quality of teaching materials that were functional and visually appealing, and a very positive perception of the benefits and implementation of the training. It was concluded that this training was effective in equipping teachers with practical skills to transform themselves into producers of digital content relevant to 21st-century learning needs.